Profound improvement : building capacity for a learning community - Mitchell, Coral, 1948- (Routledge, 2011)
The book discusses the idea of the learning community as a vehicle for professional learning and school development.As the authors show, the learning community develops in response to building capacity in three domains: personal, interpersonal and organizational. In the personal domain, educators deconstruct and reconstruct their professional narratives to enhance student learning and professional practice. In the interpersonal domain, educators generate norms and values that foster experimentation and critical analysis of educational practice and that promote collective and individu.